The American Short Story Cycle - Smith, Jennifer J. (Jennifer Joan) (Online access: OAPEN DOAB Directory of Open Access Books.)
This work spans two centuries to tell the history of a genre that includes both major and marginal authors, from Washington Irving through William Faulkner to Jhumpa Lahiri.